STRATEGI KEPALA SEKOLAH DALAM PEMBINAAN BUDAYA RELIGIUS - Wilda Arif (Kelola: Journal of Islamic Education Management, 2020)
The aims of this research are to know what is the strategy of the headmaster in fostering religious culture at SMP Negeri 13 Palopo, to know the effort of the headmaster in fostering religious culture at SMP Negeri 13 Palopo, and to know the supporting factors and hindering factors of headmaster in fostering religious culture at SMP Negeri 13 Palopo. This research is qualitative research which used pedagogic, management, and psychology approaches. The instruments used are interview guide, observation, and documentation. The data analyzed by reduction, data display and conclusion. The result of the research shows that the strategy of the headmaster in fostering religious culture at SMP Negeri 13 Palopo are planning, organizing, implementation, supervision and evaluation toward the program. The headmaster efforts in fostering the religious culture at SMP Negeri 13 Palopo such as take dhuhur and dhuha prayers together, reading al-Qur’an literacy program,  pray together before the learning process, celebrating Islamic days, implementaing 3S (sipakalebbi, sipakainge, sipakatau), and practicing asmaul huzna zikir. The supporting factor in fostering religious culture at SMP Negeri 13 Palopo are the high trust of the students’ parents to the headmaster, the good cooperation between the headmaster and the teachers in supporing the programs at school. The hidering factor is the lack of facilities and infrastructure.